New Biomarkers of Chronic Obstructive Airway Diseases: Impact on Differential Diagnosis, Therapeutic Strategies, and Prognosis in COPD. A literature review - Gawin, Konrad; Zawiślak, Wiktoria; Ignasiak, Anita; Cisowski, Michał; Dąbrowska, Maria; Rychlica, Kacper; Cholewińska-Rychlica , Jolanta; Madura, Paulina; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Chronic obstructive pulmonary disease (COPD) is a heterogeneous respiratory disorder whose diagnosis and differentiation from asthma remain challenging. The aim of this review was to present current biomarkers used in the diagnosis of COPD and to highlight promising directions for future research. A literature analysis covering the years 2020–2025 included biomarkers assessed in blood, urine, sputum, as well as genetic and molecular markers. The findings indicate that peripheral blood eosinophil counts and the neutrophil-to-lymphocyte ratio (NLR) are useful in predicting the risk of exacerbations and response to therapy. Serum proteomic and metabolomic analyses, together with urinary biomarkers, enable non-invasive patient phenotyping and early detection of exacerbations. Genetic and transcriptomic studies have identified key genes and inflammatory pathways relevant to disease pathogenesis, while the composition of the airway microbiome correlates with symptom severity and lung function. Integration of molecular, immunological, and microbiological data allows for precise patient phenotyping, supports personalized therapeutic strategies, and improves clinical outcomes. Biomarkers are becoming an important source of information in the differential diagnosis of COPD and asthma–COPD overlap (ACO), as well as in targeted treatment approaches.